Sosialisasi Anti Bullying dan Dampaknya Sebagai Upaya Pencegahan Perilaku Bullying Pada Siswa SMP Negeri 1 Ambon - Suluh Priyosahubawa; Hendri D. Hahury; Dientje Rumerung; Izaac T. Matitaputty; Hermi Oppier; Maryam Sangadji; Fredy H. Louhenapessy; Jeanee B. Nikijuluw; Sherly Ferdinandus; Djufri R. Pattilouw (I-Com: Indonesian Community Journal, 2024)
Bullying is an action carried out by someone against another person who is considered weak and can be done in various forms. Bullying that often occurs is a serious problem because it has a negative impact on the victims. There are various factors that cause someone to commit acts of bullying. Some examples of these factors include problems in the family, school factors that do not pay attention to students properly, environmental factors and media factors that are not educational. Through community service activities regarding anti-bullying education at SMP Negeri 1 Ambon, it is hoped that students can form good character and have a high social spirit in the SMP Negeri 1 Ambon school environment. This socialization activity was carried out on October 27 2023 using the counseling method which was attended by 35 students and 3 accompanying teachers. This activity ran very smoothly and conducively and students and teachers were very active in participating. The results of this outreach activity show an increase in knowledge regarding bullying and prevention. This can be seen from the number of students who were able to answer questions from the presenter very well.